On (not) becoming machine: countering algorithmic thinking through digital performance art - Putnam, EL (Frontiers in Communication, 2024)
Regular engagement with technologies through habit enables these to infiltrate our lives as we are constituted through our machines. This provocation underpins the digital performance art works Ghost Work and Friction, which involve creative repurposing of everyday digital technologies as poetic operations, presenting an embodiment of algorithms that engages with their performativity. The execution of these performance algorithms are interventions into data collection, crafting feminist fabulations in the algorithmic empire of what Couldry and Mejias refer to as data colonialism. Using methods of data feminism in conjunction with Hui's philosophy of technology, these performances cultivate aesthetic experiences that are multifaceted instances of data visceralization. Ghost work and Friction use artistic idioms thick with meaning, reflexively engaging with processes of contingency and recursivity present in human-technological relations. The resulting digital performances are aesthetic experiences that are affective and ambivalent, introducing alternative logics to hegemonic algorithmic thinking that emphasizes extraction and optimization.